2018
DOI: 10.1113/jp276015
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural basis of strong unitary inhibition in a binaural neuron

Abstract: Binaural neurons in the lateral superior olive (LSO) integrate sound information arriving from each ear, and powerful glycinergic inhibition of these neurons plays an important role in this process. In the present study, we investigated the ultrastructural basis for strong inhibitory inputs onto LSO neurons using serial block face scanning electron microscopy. We reconstructed axon segments that make contact with the partially reconstructed soma and proximal dendrite of a mouse LSO neuron at postnatal day 18. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…; Hruskova et al . ), thus creating large quantal amplitudes (Kim & Kandler, ), and the elaboration of multiple active zones by inhibitory axons enabling the generation of multiquantal IPSCs (Gjoni et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Hruskova et al . ), thus creating large quantal amplitudes (Kim & Kandler, ), and the elaboration of multiple active zones by inhibitory axons enabling the generation of multiquantal IPSCs (Gjoni et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The number of repeated varicosities per axon, and therefore also the total number of active zones, strongly varied between individual axons. This, together with a constant quantal size between ‘small’ and ‘large’ unitary IPSCs estimated by the Sr 2+ method (Gjoni et al ., ), strongly suggests that ‘small’ and ‘large’ unitary IPSCs are primarily distinguished by the number of active zones that they establish with an LSO neuron. Furthermore, when studying younger LSO neurons with fibre stimulation, we found that the characteristic ∼10‐fold variation between inputs is already found at ∼P7, despite an overall weaker total inhibition strength in pre‐hearing mice (smaller maximal IPSCs; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Gjoni et al . (, b ) have carried out an elegant analysis of synaptic integration at the neurons in the lateral superior olive (LSO). At this site, excitatory inputs and inhibitory inputs are received that originate from the ipsi‐ and and contralateral ears, respectively.…”
mentioning
confidence: 99%
“…Gjoni et al . (, b ) addressed these questions by a combination of optogenetics, electron microscopy, model simulation and electrophysiology.…”
mentioning
confidence: 99%
See 1 more Smart Citation